Associations among temporal and large artery abnormalities on vascular ultrasound in giant cell arteritis. (3rd September 2021) - DiIorio, MA; Sobiesczcyk, PS; Xu, C; Huang, W; Ford, JA; Zhao, SS; Solomon, DH; Docken, WP; Tedeschi, SK
Abstract : Objectives : Giant cell arteritis (GCA) can manifest in cranial and/or extracranial arteries. We investigated the distribution of affected arteries on vascular ultrasound (VUS) among patients with new-onset or prior-onset GCA. Method : We retrospectively studied patients with either new-onset or prior-onset GCA and an abnormal VUS, from 2013 to 2017. Trained vascular technologists imaged the bilateral temporal arteries and carotid, axillary, and subclavian arteries. Vascular medicine physicians interpreted the images. Vasculitis-related abnormalities in individual vessels and their distribution (temporal artery, large artery, or both) were evaluated. Phi coefficients (φ) and Fisher's exact test were used to assess correlations among individual abnormal arteries. Results : Among 66 GCA patients, 28.8% had prior-onset GCA (median duration 17.8 months). Acute arteritis on VUS was observed in the majority of patients with both new-onset (72.3%) and prior-onset GCA (68.4%); the remainder had hyperechoic wall thickening without acute arteritis. Involvement of the temporal arteries only (45.5%) or large arteries only (34.8%) was more common than involvement of both (19.7%); this finding was similar in new-onset and prior-onset GCA. There were moderate positive correlations among temporal artery branches (φ = 0.51–0.58, p < 0.003) and among axillary and subclavian arteries (φ = 0.51–0.77, p < 0.003), and moderate negative correlations between abnormalities in the temporal and large arteries (φ = −0.46 to −0.58, p < 0.003). Conclusion : On VUS, vasculitis-related abnormalities in the temporal arteries only or large arteries only were more common than concurrent temporal and large artery abnormalities in patients with both new-onset GCA and prior-onset GCA.